RETROSPECTIVE AND PROSPECTIVE ANALYSIS OF FOREIGN ECONOMIC ACTIVITY OF UKRAINE - KARVATSKA, Natasha; TIURINA, Nila; NAZARCHUK, Tatiana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
A retrospective analysis and assessment of the current state of Ukraine’s foreign economic activity during the years of independence was performed in the article. In particular, the volume of export-import and investment activities, indicators of economic openness, geographical and commodity structure of exports and imports were analyzed. According to the results of the analysis, it was determined that in the process of independence and development of the national economy of Ukraine there is a transformation into an open economic system that tries to take advantage of international economic cooperation, develop all forms of international economic relations. However, due to inefficient international specialization, slow restructuring of the national economy, inefficient foreign trade management, the level of competitiveness and investment attractiveness of Ukraine in the world market remains low. The export-oriented model of economic growth with the predominance of low-tech exports has led to the extensive nature of economic development, which remains energy-intensive, low-productive, poorly diversified, uncompetitive and dependent on external sources of raw materials, energy resources and world markets. It is positive that Ukraine has changed the vector of orientation in foreign economic activity and the European Union is gradually becoming the largest and main foreign trade partner. Such a trend, given the geopolitical, geo-economics and historical European position of Ukraine, should remain one of the priorities of Ukraine’s foreign economic policy. The article concludes that the system of foreign economic regulation of Ukraine needs radical changes, which should begin with a review of foreign economic policy of the state which should be aimed at increasing export potential, product diversification, introduction of innovative technologies to ensure a sufficient level of competitiveness of domestic goods in world markets.